2016
DOI: 10.1108/aia-06-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Autism and offending behaviour: needs and services

Abstract: Purpose Autism spectrum disorder (ASD) brings out the limitations of the Criminal Justice Service. The purpose of this paper is to review some of the salient issues and their remedies. Design/methodology/approach A narrative review based on the literature and the clinical experience of the authors. Findings ASD’s hidden disabilities, even without the frequent coexistence of other disorder, derail the standard responses to offending. Practical implications Management of these individuals as offenders depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Risk assessment and treatment approaches for this group of individuals were suggested to be related to co-morbid psychopathology, rather than traits associated with ASD, a finding echoed in existing research ( Mouridsen, 2012 ). Indeed, it has previously been demonstrated that individuals with ASD are no more likely ( Hippler et al, 2010 ) or in fact less likely to commit criminal offences compared to those without ASD ( Im, 2016 ), suggesting that the traits associated with ASD are not necessarily pre-disposing factors for offending behaviour ( Pearce & Berney, 2016 ). Rather, the findings from this study highlight there are potentially alternative factors likely to contribute towards violence and risk of offending in this population (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Risk assessment and treatment approaches for this group of individuals were suggested to be related to co-morbid psychopathology, rather than traits associated with ASD, a finding echoed in existing research ( Mouridsen, 2012 ). Indeed, it has previously been demonstrated that individuals with ASD are no more likely ( Hippler et al, 2010 ) or in fact less likely to commit criminal offences compared to those without ASD ( Im, 2016 ), suggesting that the traits associated with ASD are not necessarily pre-disposing factors for offending behaviour ( Pearce & Berney, 2016 ). Rather, the findings from this study highlight there are potentially alternative factors likely to contribute towards violence and risk of offending in this population (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an increasing number of studies which examine sexual offending behaviour in ASD individuals (e.g. Allen et al, 2008;de la Cuesta, 2010;King & Murphy, 2014;Pearce & Berney, 2016), there has been a lack of research investigating stalking and ASD. The present study carried out a scoping review following PRISMA guidelines in order to identify studies which have been carried out exploring stalking behaviour in individuals with ASD or subthreshold ASD (e.g., Peters et al, 2015;Munn, Peters, Stern, Tufanaru, McArthur, & Aromataris, 2018).…”
Section: Present Reviewmentioning
confidence: 99%
“…There is some evidence that individuals with ASD may be over represented in specialist forensic mental health or learning disability settings, with reported rates between 1.5 and 30 per cent (Scragg and Shah, 1994;Alexander et al, 2011;Esan et al, 2015). Furthermore, offenders with ASD expose the limitations of the Criminal Justice Service and the dependence of effective management of these individuals on awareness of and appropriate adaptation to, these limitations (Pearce and Berney, 2016). It is also recommended that an empirical study of the women residents in the special hospitals be implemented (Lai et al, 2015).…”
Section: Diagnosis In Womenmentioning
confidence: 99%